PENGARUH PENAMBAHAN TEPUNG UDANG REBON TERHADAP PERTUMBUHAN DAPHNIA MAGNA SEBAGAI PAKAN ALAMI BIBIT IKAN - Hidayat, Mohamad Rusdi (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2014)
One of the problems in the development of fish breeding in West Kalimantan is the difficulty in feeding the newly hatched fish. Daphnia magna is a favorite species used for feeding fish or shrimp larvae D. magna cultivation technique which is simple and low cost need to be developed. This study aims to determine the effect of rebon shrimp powder on the growth of D. magna. The methods used were media preparation, propagation of D. magna culture, and cultivation of D. magna at various concentrations of shrimp powder. The results showed that the addition of 10 ppm shrimp powder in green water medium could increase the population of D. magna up to 260% in 7 days. The addition of shrimp powder could also increase the protein content of D. magna up to 78, 29%.